Discussion on treatment courses of brucellosis with spondylitis - a report of two cases. (2023) - Yang, Zhi; Wu, Weigang; Ou, Pengcheng; Zeng, Furong; Xie, Dongyuan; Yang, Lin; Yang, Guilin; Zhou, Boping
Abstract: Human Brucellosis is a zoonotic contagious disease caused by Brucella infection and is common throughout the world, which can travel through the bloodstream to various organs. Brucellar spondylitis(BS) is the foremost cause of brucellosis's debilitating and disabling complications. We report two sisters with brucellosis complicated by lumbar spondylodiscitis accompanied by cold abscess formation. The diagnosis was based on their symptoms, epidemiological characteristics, laboratory and magnetic resonance imaging(MRI) results. Our therapeutic strategy in these two cases indicate that drug combination and prolongation of the use of antibiotics is a therapeutic strategy worthy of popularizing to reach a greater clearance rate of the infection. Highlights: Brucellosis gradual increased along with the development of animal husbandry. BS is the foremost cause of brucellosis's debilitating and disabling complications. Drug selection and duration of antibiotic therapy remain controversial. Prolongation course of treatment is a therapeutic strategy worthy of popularizing. The need for surgical treatment should be carefully considered.